Exogenous Glutathione Increases Arsenic Translocation Into Shoots and Alleviates Arsenic-Induced Oxidative Stress by Sustaining Ascorbate–Glutathione Homeostasis in Rice Seedlings - Jung, Ha-il; Kong, Myung-Suk; Lee, Bok-Rye; Kim, Tae-Hwan; Chae, Mi-Jin; Lee, Eun-Jin; Jung, Goo-Bok; Lee, Chang-Hoon; Sung, Jwa-Kyung; Kim, Yoo-Hak (Frontiers in Plant Science, 2019)
Glutathione (GSH) plays diverse roles in the physiological processes, stress defense, growth, and development of plants. This study investigated the effects of exogenous GSH on the biochemical responses of reactive oxygen species and antioxidant levels in rice (Oryza sativa L. cv Dasan) seedlings under arsenic (As) stress. As treatment inhibited the growth; increased the level of superoxide, hydrogen peroxide, and malondialdehyde; and enhanced the uptake of As by the roots and shoots in hydroponically grown 14-day old seedlings. Furthermore, it reduced GSH content and GSH redox ratios, which have been correlated with the decrease in ascorbate (AsA) redox state. Whereas, the exogenous application of GSH in As-treated seedlings reduced As-induced oxidative stress, improved antioxidant defense systems by maintaining antioxidant and/or redox enzymes homeostasis and increased the AsA and GSH contents. The GSH application also increased the As translocation from the roots to the shoots. These results indicated that the increase in GSH redox state can be linked to an increase in the AsA redox ratio via the induction of the AsA-GSH cycle. Therefore, the results suggest that exogenous GSH application should be a promising approach to enhance As-stress resistance in rice plants.